Tuning the Mechanical and Adsorption Properties of Silica with Graphene Oxide. Issue 10 (30th July 2014) - Singh, Vivek K.; Cura, M. Erkin; Liu, Xuwen; Johansson, Leena‐Sisko; Ge, Yanling; Hannula, Simo‐Pekka
Abstract: Silica and graphene oxide (GO) were synthesized by modified Stöber and Hummer's methods, respectively. Silica/GO composite powders of different compositions were obtained by introduction of GO sheets in between silica particles through a hydrothermal synthesis. Composites were characterized by Fourier transform infrared spectroscopy, X‐ray diffraction analysis, and scanning and transmission electron microscopy. Density measurements were performed with a pycnometer and chemical analyses of powders were performed by energy‐dispersive X‐ray and X‐ray photoelectron spectroscopies. Composite powders showed an improvement in the Cu 2+ ion adsorption property relative to pure silica. Composite powders were further consolidated at 1200 °C under 50 MPa pressure in vacuum by pulsed electric current sintering. Transparency in the UV/Vis region, the electrical conductivity, and the toughness of consolidated samples were altered by varying the GO content in the starting materials. Studies suggest that the use of GO as a reinforcing agent not only improves the mechanical properties of transparent silica ceramic, but also improves the electrical conductivity and adsorption properties of silica. Abstract : Get set, GO! Silica/graphene oxide (GO) composite powders of various compositions have been synthesized and compacted by spark plasma sintering. The optical and mechanical properties of silica were tuned by varying the GO content (see figure). Improved fracture toughness occurred with increasing amount of GO. Powders were also applied to Cu removal from water; the adsorption properties of silica were improved with a high concentration of GO.